Independent component analysis of MODIS-NDVI data in a large South American wetland - Antico, Andres (2012)
Monthly images of Normalized Difference Vegetation Index (NDVI) from the moderate resolution imaging spectroradiometer (MODIS) are used to characterize the spatio-temporal variability of vegetation in a large South American wetland (SAW) (located in the Paraná River floodplain) during the period 2000-2009. While these data do not meet the requirements of classical component extraction techniques (CETs) (e.g. principal component analysis (PCA)), they are suitable for the modern method named independent component analysis (ICA). Hence, ICA is used here to extract three statistically independent modes of inter-annual MODIS-NDVI variability that are successfully interpreted as vegetation responses to hydrological changes. One mode isolates the vegetation response to a severe drought associated with La Niña 2007-2008. Another component reflects the expansion (or contraction) of lagoons owing to high (or low) water level of the Paraná River. The remaining mode captures the vegetation decrease caused by the flood related to El Niño 2006-2007. The results presented here for a particular wetland suggest that ICA of NDVI images is a powerful tool for identifying the physical causes of vegetation changes in other large wetlands. © 2011 Taylor & Francis.